Evaluation of the proteolytic potential of bacteria isolated from the Iranduba soil (Research, Society and Development, 2021)
Bacteria are groups of microorganisms that live independently or in community. They are found in several types of ecosystems, and constitute the most numerous and important group, as they degrade certain substrates generating compounds of high commercial value, among these substrates, enzymes such as lipase, amylase and protease, among others, are used in various processes industrial. Bacteria are considered an attractive source in the production of protease, due to the possibility of cultivation in fermentation processes with reduced time and high volumes. The aim of the present study was to isolate bacteria that produce proteolytic enzymes and evaluate their enzymatic potential. For this, soil samples collected from the municipality of Iranduba, located in the State of Amazonas, were analyzed. From the microorganisms obtained, two bacteria were selected, which were grown on gelatin milk agar to determine proteolytic activity. According to the results obtained, the activity was determined by the formation of degradation halos around the colonies, which were measured, analyzed and represented according to the classification of proteolytic activity. The formation of these halos was synonymous with the existence of proteolytic activity , where the isolated bacteria produced enzymes with degradation power in relation to the protein present in the milk used in the culture medium.